DNA-PKcs, a player winding and dancing with RNA metabolism and diseases - Jiabao Hou; Mingjun Lu; Jingwei Guo; Jinghong Wu; Chenyang Wang; Ping-Kun Zhou; Teng Ma (Cellular & Molecular Biology Letters, 2025)
Abstract The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is a key kinase in the DNA repair process that responds to DNA damage caused by various factors and maintains genomic stability. However, DNA-PKcs is overexpressed in some solid tumors and is frequently associated with poor prognosis. DNA-PKcs was initially identified as a part of the transcription complex. In recent years, many studies have focused on its nonclassical functions, including transcriptional regulation, metabolism, innate immunity, and inflammatory response. Given the pleiotropic roles of DNA-PKcs in tumors, pharmacological inhibition of DNA-PK can exert antitumor effects and may serve as a potential target for tumor therapy in the future. This review summarizes several aspects of DNA-PKcs regulation of RNA metabolism, including its impact on transcriptional machinery, alternative splicing, and interaction with noncoding RNAs, and provides insights into DNA-PKcs beyond its DNA damage repair function.